The Role of Social Media Towards Political Accountability in Pakistan: A Literature Review - Sadiq, Saiqa (European Centre for Research Training and Development UK, 2018)
Democracy is globally accepted form of government, especially when the technological development going to make this world a global village. Scholars think about the ideas of global democratic government, wherein short fall of democracy is ill-fated. However, political accountability is the essential characteristics of democracy and it cannot flourish without it. This paper adopts a qualitative approach by using qualitative content analysis and observation over social networking sites (SNS), in which democracy, accountability, and freedom of expression will extensively use. The extensive literature review indicates that social media facilitates the freedom of expression, provides opportunities of direct political participation, improves the electoral process and increase political accountability in authoritarian countries and emerging democracies. However, an emerging democracy like Pakistan, where social media trend is up surging and accountability condition is destitute. It is highly justified to investigate the role of social media towards political accountability